Formulation and Evaluation of SNEDDS Loaded with Original Lipophenol for the Oral Route to Prevent Dry AMD and Stragardt's Disease - Maxime Vincent; Laurianne Simon; Philippe Brabet; Philippe Legrand; Christophe Dorandeu; Josephine Lai Kee Him; Thierry Durand; Céline Crauste; Sylvie Begu (MDPI AG, 2022)
Dry age-related macular degeneration (Dry AMD) and Stargardt's disease (STGD1) are common eye diseases, characterized by oxidative and carbonyl stress (COS)-inducing photoreceptor degeneration and vision loss. Previous studies have demonstrated the protective effect of photoreceptors after the intravenous administration of a new lipophenol drug, phloroglucinol-isopropyl-DHA (IP-DHA). In this study, we developed an oral formulation of IP-DHA (BCS Class IV) relying on a self-nanoemulsifying drug delivery system (SNEDDS). SNEDDS, composed of Phosal® 53 MCT, Labrasol®, and Transcutol HP® at a ratio of 25/60/15 (w/w/w), led to a homogeneous nanoemulsion (NE) with a mean size of 53.5 ± 4.5 nm. The loading of IP-DHA in SNEDDS (SNEDDS-IP-DHA) was successful, with a percentage of IP-DHA of 99.7% in nanoemulsions. The in vivo study of the therapeutic potency of SNEDDS-IP-DHA after oral administration on mice demonstrated photoreceptor protection after the induction of retinal degeneration with acute light stress (73-80%) or chronic light stress (52-69%). Thus, SNEDDS formulation proved to increase the solubility of IP-DHA, improving its stability in intestinal media and allowing its passage through the intestinal barrier after oral force-fed administration, while maintaining its biological activity. Therefore, SNEDDS-IP-DHA is a promising future preventive treatment for dry AMD and STGD1.